2014
DOI: 10.1093/pa/gsu015
|View full text |Cite
|
Sign up to set email alerts
|

The Economic and Electoral Consequences of Austerity Policies in Britain

Abstract: The aim of this paper is to examine the relationship between electoral support and the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Britain is undergoing the most extensive reduction and restructuring of its welfare state since the Second World War (Yeates, Haux et al 2011); (Taylor-Gooby and Stoeker 2010); (Taylor-Gooby 2011); (Whitely, Clarke et al 2014). During the five-year Conservative-Liberal Democrat Coalition Government from 2010 to 2015, £80 billion spending cuts were announced that included £18 billion reduction in welfare spending (Brewer and Browne 2011 4).…”
Section: Context Cases and Methodsmentioning
confidence: 99%
“…Britain is undergoing the most extensive reduction and restructuring of its welfare state since the Second World War (Yeates, Haux et al 2011); (Taylor-Gooby and Stoeker 2010); (Taylor-Gooby 2011); (Whitely, Clarke et al 2014). During the five-year Conservative-Liberal Democrat Coalition Government from 2010 to 2015, £80 billion spending cuts were announced that included £18 billion reduction in welfare spending (Brewer and Browne 2011 4).…”
Section: Context Cases and Methodsmentioning
confidence: 99%
“…A similar report in 2014 found very similar figures [24]. With welfare and immigration regularly ranking high on election priorities [31] this shows that the media have not adequately informed the public of the information they need to properly participate in democracy.…”
Section: Introductionmentioning
confidence: 90%
“…Using data for the period 2004-2013, Whiteley et al (2015) assessed how each government's rating for economic management correlated with political support, measured by voting intentions. They found that there had been a strong relationship during Labour's term of office but, at the time they did their analysis, the Coalition did not appear to be benefiting from the nascent improvement in the economy.…”
Section: Competence and Partisanshipmentioning
confidence: 99%